KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING PENGARUH R&D DAN INTANGIBLE ASSET PADA NILAI PERUSAHAAN - Kuniawati, Rina; Asyik, Nur Fajrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to examine the influence of research and development and intangible assets to the firm value (PBV); financial performance (ROA) as the intervening variable through corporate annual reports which have been prepared by the manufacturing companies which are listed in Indonesia Stock Exchange. The population in this research has been obtained by using purposive sampling method in 2013-2015 periods and based on the predetermined criteria, 11 manufacturing companies have been obtained as samples. The analysis method which has been applied in this research is multiple linear regression analysis with the SPSS (Statistical Product and Service Solutions) application instrument. The result of the research shows that (1) the intensity of research and development gives positive influence to the financial performance; (2) intangible asset gives positive influence to the financial performance; (3) the intensity of research and development does not give any influence to the firm value; (4) intangible assets does not give any influence to the firm value; (5) financial performance gives positive influence to the firm value; (6) financial performance mediates the intensity of research and development and intangible asset to firm value.Keywords: financial performance, intensity of research and development, intangible assets, and firm value.